2017
DOI: 10.1126/science.aal3496
|View full text |Cite
|
Sign up to set email alerts
|

Xenon isotopes in 67P/Churyumov-Gerasimenko show that comets contributed to Earth's atmosphere

Abstract: The origin of cometary matter and the potential contribution of comets to inner-planet atmospheres are long-standing problems. During a series of dedicated low-altitude orbits, the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA) on the Rosetta spacecraft analyzed the isotopes of xenon in the coma of comet 67P/Churyumov-Gerasimenko. The xenon isotopic composition shows deficits in heavy xenon isotopes and matches that of a primordial atmospheric component. The present-day Earth atmosphere con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(240 citation statements)
references
References 33 publications
7
221
1
Order By: Relevance
“…It has been concluded that the difference between solid and volatile phase points to a not-homogenized protosolar nebula from which comets are thought to have emerged. This is supported by the detection of non-solar isotopic ratio for xenon (Marty 2017) and Si (Rubin 2017) in comet 67P by ROSINA.…”
Section: O N C L U S I O Nmentioning
confidence: 53%
See 2 more Smart Citations
“…It has been concluded that the difference between solid and volatile phase points to a not-homogenized protosolar nebula from which comets are thought to have emerged. This is supported by the detection of non-solar isotopic ratio for xenon (Marty 2017) and Si (Rubin 2017) in comet 67P by ROSINA.…”
Section: O N C L U S I O Nmentioning
confidence: 53%
“…This however would be hard to explain. ROSINA has detected a non-solar isotopic ratio for xenon (Marty 2017) as well as for Si (Rubin 2017) in comet 67P, which points to a non-homogeneously mixed protosolar nebula. In addition, a high D 2 O/HDO versus HDO/H 2 O ratio (Altwegg 2017) and molecular oxygen, which seems to be very well embedded in water (Bieler et al 2015), have been measured in the coma of 67P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with noble gas measurements from the returned sample, we would be able to determine the likelihood that the MBCs are the sources of Earth's water. We could also be able to constrain the cometary contribution further, complementing results based on Rosetta data (Marty et al, 2016(Marty et al, , 2017. In each case, when combined with data from the sample return and in-situ study performed by Caroline, we would be provided with information to help constrain where in the Solar System the MBCs formed relative to comets, S-and C-type asteroids.…”
Section: Introductionmentioning
confidence: 94%
“…Also important is to develop a relatively simple scenario, trying to follow the Occam's razor and avoid speculative hypothetical approaches. The sources and processes responsible for delivery of major volatile elements, mainly concentrated in the atmo-hydrosphere, are not considered here and the readers can find the respective data and discussions in recent papers by Marty [2012], Albarede et al [2013], Dauphas and Morbidelli [2014], Marty et al [2016Marty et al [ , 2017, FischerGödde and Kleine [2017].…”
Section: Terrestrial Reservoirsmentioning
confidence: 99%